A Creativity Based Goal Modeling Approach for Accessibility of Neurodivergent Individuals - Bia, André Alexandre Dias (2023)
Equality and equity for all kinds of people are fundamental human rights. One movement that strives for those rights in the context of neurological differences is neurodiversity. It’s a term that represents the acceptance and respect of diverse neurological conditions, such as ASD (Autism Spectrum Disorder), ADHD (Attention Deficit Hyperactivity Disorder), Dyslexia, and others, like any other human differences that distinguish us all. Such a topic points to the importance of embracing these differences in society. However, this is still a distant reality. Neurodivergents are often victims of stigma and prejudice in a world that excludes those that don’t fit a strict definition of "normal", making this group prone to unemployment or lower levels of education. Despite the difficulties that those within the neurodiversity community face, be it from their own condition or society’s neurotypical prevalence, the same characteristics that distinguish them from everyone else can also be beneficial and valuable to the workplace. This can be from not only an inclusive perspective but also competition-wise, as they can bring their unique skills and innovation when aligned with their interests. When it comes to computer science, neurodivergents, especially those with ASD, are quite attracted to this area of engineering as a career option. This dissertation will bring focus to software engineers who are neurodivergent with the goal of making some requirements engineering tasks more accessible to them. Through a systematic literature review, we understood what research has been done to tackle neurodiversity in the context of software engineering, and used it as a basis for our neurodivergent-inclusive creativity-based goal modeling approach. The proposed solution resulted in an accessible tool for neurodivergent software en- gineers that covers the requirements elicitation and requirements analysis tasks while respecting Human-Computer Interaction guidelines for neurodivergent individuals. The resulting approach covers the struggles that neurodivergent engineers face when using engineering tools, while also addressing one of the core strengths found in neurodiver- gency, that being creativity. To achieve this, the approach bases on creativity techniques along with an iStar extension that facilitates the translation of ideas generated from those techniques to standard iStar elements. We applied the concepts of the approach to develop the prototype of a neurodivergent-inclusive tool called IdeaStar. The concepts of the approach along with the IdeaStar tool were empirically evaluated with respect to usefulness and ease of understanding by a group of 25 participants and the results were positive.